KONSEP JILBAB DALAM PRESPEKTIF AL-QUR’AN - Susanti Susanti; Eni Fatriyatul Fahyuni (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
This research is based on the lack of understanding of society in general, especially Muslim women about the concept of the hijab that is in accordance with Islamic Sharia, and also an error in understanding the meaning of the hijab, jilbab, and khimar. Because most of them assume that all three terms have the same meaning. In addition, it is also due to the emergence of various variations of hijab models at this time, most of which are incompatible with Islamic law. So that not a few Muslim women who wear jilbab but their genitals are still visible, because they only make jilbab a fashion trend and part of a lifestyle, without paying attention to dress in accordance with Islamic law, as written in the Al-Qur’an.This type of research is library research can also be called a qualitative of literal. In this case the first step that must be taken is to gather material related to the concept of the jilab in the perspective of the Qur’an. Then the materials are analyzed as a source of ideas to explore new ideas or ideas, as a basis for deduction from existing knowledge, so as to develop a new theoretical framework, or can be used as a basis for problem solving. Then the last activity is to present the results of the analysis.The results of the study can be concluded that the sharia jilab contained in the word of Allah in the Quran surah Al-Ahzab verses 33 and59, Al-A'raf verses 26 and 31, and an- Nur verse 31, and also in As-sunnah. The proofs of the Quran and As-Sunnah illustrate that the principle of jilbab that should be worn by Muslim women is that they must: be able to cover the entire body except the face and palms, the fabric used must be thick, loose, and not tight, clothing should not resembling the clothes of the opposite sex and the clothes of infidels, clothes should also not be perfumed, nor should they be intended for decoration and not popularity clothing. That is the purpose is to protect and maintain the honor of Muslim women and also so that they are young to be recognized.